Kinematic analysis of human gait cycle - Abbass, Sadiq Jafer; Abdulrahman, Ghaidaa (Nahrain University College of Engineering Journal, 2017)
Kinematic system is used in gait analysis to record the position and orientation of the body segments, the angles of the joints and the corresponding linear and angular velocities and acceleration. Gait analysis is used for two very different purposes to aid directly in the treatment of individual patients and to improve our understanding of gait through research. The purpose of the study is to show an ideal kinematics appearance of human gait cycle for walking in order to get measurement values that can be depended on in the hospitals of rehabilitation, the centers of physical therapy and the clinical of medical sports as a reference data for kinematic joint parameter. In this study, 20 subjects and one abnormal subject (undergoes foot flat) were selected from the society; the 20 subjects were not to have any pathology that would affect gait and had to be unfamiliar with treadmill walking, then a video recording was made for them by using a single digital video camera recorder fitted on a stand of three legs in a sagittal plane while subjects walked on a motorized treadmill one by one, the treadmill is often used in rehabilitation programs because it allows standard and controlled conditions and it needs small space. Then by special motion analysis software (Dartfish) was used to study the knee and hip joint kinematics and the spatial –temporal gait parameters (step length, stride length, stride duration, cadence) from the video recording. Results obtained from the Dartfish program are important in understanding that the knee and hip angles differ in each gait cycle, similarly to spatial- temporal parameters, the spatial- temporal parameters differ in each gait cycle analyzed for subjects.